2017
DOI: 10.1123/ijspp.2015-0631
|View full text |Cite
|
Sign up to set email alerts
|

Physical Predictors of Elite Skeleton Start Performance

Abstract: Only 3 physical-test scores were needed to obtain a valid and stable prediction of skeleton start ability. This method of isolating independent physical variables underlying performance could improve the validity and efficiency of athlete monitoring, potentially benefitting sport scientists, coaches, and athletes alike.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
19
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 19 publications
(26 citation statements)
references
References 16 publications
(18 reference statements)
1
19
0
Order By: Relevance
“…19 A similar data reduction process has recently been undertaken to identify key performance variables in an elite sport setting. 20 Variables within a given principal component are correlated with each other, while the principal components themselves do not correlate and so explain distinct information. 21 The PCA was performed using IBM SPSS Statistics for Windows (Version 20.0, Armonk, NY, USA).…”
Section: Resultsmentioning
confidence: 99%
“…19 A similar data reduction process has recently been undertaken to identify key performance variables in an elite sport setting. 20 Variables within a given principal component are correlated with each other, while the principal components themselves do not correlate and so explain distinct information. 21 The PCA was performed using IBM SPSS Statistics for Windows (Version 20.0, Armonk, NY, USA).…”
Section: Resultsmentioning
confidence: 99%
“…In the correlational analysis with performance, special attention was given to the variables most strongly related to each component extracted from the PCA (Colyer et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…The use of PCA helps in the analysis of the large amount of information obtained from the measurement of many variables in attempts to find possible relationships with sports performance (Colyer et al, 2017), but attention must be paid to the conditions of application of statistical procedures. To continue with the determination of predictive variables of performance in CrossFit, it would be necessary to include new variables or more specific tests and new capacities (e.g.…”
mentioning
confidence: 99%
“…Acceleration and high speed at the end of the start phase are crucial for high bob speed during a race and a better overall result [50,51]. At the start phase, athletes must start the race by pushing the bob within 60 seconds after the start signal and run at full speed about 55 m. The start and push phases last for only 6 seconds, but they are the most important for the final result [52]. To perform a push-start, leg extensors must generate high mechanical power in the hip, knee and ankle joints to create significant horizontal propulsive force that propels the athlete's body and bob forward.…”
Section: Bobsleighingmentioning
confidence: 99%
“…Previous studies reporting the electromyographic (EMG) activity in sprinters in the acceleration phase have shown that biceps femoris (RF) is one of the most important muscles for developing maximum speed [53]. Similar as at the start of a sprint run, the longer running distance increased workload of the plantar ankle flexors [52].…”
Section: Bobsleighingmentioning
confidence: 99%